1999
DOI: 10.1046/j.1439-0418.1999.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal variation in foliar chemistry and anatomy of yunnan pine, Pinus yunnanensis, and pine sawfly (Hym., Diprionidae) performance

Abstract: Host plant characteristics associated with the larval feeding performance of a pine saw~y were examined across an altitudinal gradient in south!western China[ Neodiprion xiangyunicus "Xiao and Huang# larval performance "e[g[ larval mass and potential fecundity# and defoliation intensity increased at higher altitudes along an altitudinal gradient in Sichuan\ China[ Needle chemistry and anatomy of yunnan pine\ Pinus yunnanensis "Franch[#\ also varied across along an altitudinal gradient[ In general\ total sesqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 35 publications
2
38
0
3
Order By: Relevance
“…It is likely that within canopy migration is guided by food quality of the needles that allows optimization of intake of specific elements or substances. This conclusion is supported by other studies in which feeding preferences of insects were attributed to foliage chemistry (Björkman, 1997;Hengxiao et al, 1999;Wright et al, 2003;Keeling and Bohlmann, 2006). Moreau et al (2003) found that under natural conditions balsam fir sawfly (Neodiprion abietis) larvae prefer the 2-year-old needles of Abies balsamea, despite the fact that in experimental conditions they had the best performance on a mixed diet (all needle age classes).…”
Section: Discussionsupporting
confidence: 65%
“…It is likely that within canopy migration is guided by food quality of the needles that allows optimization of intake of specific elements or substances. This conclusion is supported by other studies in which feeding preferences of insects were attributed to foliage chemistry (Björkman, 1997;Hengxiao et al, 1999;Wright et al, 2003;Keeling and Bohlmann, 2006). Moreau et al (2003) found that under natural conditions balsam fir sawfly (Neodiprion abietis) larvae prefer the 2-year-old needles of Abies balsamea, despite the fact that in experimental conditions they had the best performance on a mixed diet (all needle age classes).…”
Section: Discussionsupporting
confidence: 65%
“…However, in this study, northern, western, and lower elevation sites included some of the wettest and warmest sites, including the CWH and ICH zones. Indeed, prior studies observed that greater pest activity at lower elevations was associated with plants having increased levels of SMs (e.g., Hobbs and Partridge, 1979;Hengxiao et al, 1999;Heineman et al, 2010), and the CWH and ICH sites were at the lowest elevations of all the sites sampled.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, larval and cocoon masses of a pine sawfly, Neodiprion xiangyunicus (Xiao & Huang), feeding on Yunnan pine (Pinus yunnanensis Franch.) were found to increase with elevation in south-western China (Hengxiao et al 1999). McMillin et al (1996) observed that pine defoliation by the sawfly Neodiprion autumnalis (Smith) was present only at elevations of 2410-2440 m a.s.l.…”
Section: Topography Effectsmentioning
confidence: 99%
“…Elevation not only acts as a physical boundary limiting the distribution of defoliators and host trees but it also affects local climatic conditions (temperature, precipitation, wind speed and radiation) and influences insect physiology and performance (Hodkinson 2005). Natural enemy abundance and hostspecies nutritional value and distribution can also vary with elevation and have an impact on defoliator tree damage and insect performance (Niemelä et al 1987, McMillin et al 1996, Hengxiao et al 1999, Kharuk et al 2007). Steep, especially south to west-facing slopes, are generally drier, warmer and have more nutrient deficient conditions than other slopes, and can result in more stressed host trees and possibly more favorable local climates and habitats for defoliators (Morse & Kulman 1986, Kharuk et al 2007).…”
Section: Introductionmentioning
confidence: 99%